Portrait of the Healthy Family in Banyuwangi District, Indonesia: Implementation Evaluation of the Healthy Indonesia Program with Family Approach (PIS-PK) - Syifa’ul Lailiyah; Diansanto Prayoga; Jayanti Dian Eka Sari; Siti Nuraini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Healthy Indonesia Program with Family Approach (PIS-PK) implementation is a way to implement Minimum Service Standards (SPM) in the health sector through family empowerment. The achievement of families visited in Banyuwangi District in 2017-2019 was 42%. Healthy Family Index (IKS) Banyuwangi is 0.08 (unhealthy category). That IKS is the second lowest value in East Java Province in 2019. Six PIS-PK indicators are far from the total coverage. The study purpose is to evaluate the implementation of PIS-PK based on the PIS-PK Regulation of the Minister of Health Republic of Indonesia Number 39 of 2016. The type of research is descriptive exploratory research. The study was conducted in 10 PHC and the Banyuwangi DHO. The informants are the PIS-PK coordinator at the PHC, head of the PHC, and the team of PIS-PK at the Banyuwangi DHO. This study uses primary data and secondary data. Primary data obtained from in-depth interviews and Focus Group Discussions. Analyzing research data descriptively and thematic content approach. The stage of family visits and initial intervention has been carried out by PHC quite well. At the family visit stage, the data collection team has various perceptions of healthy family instruments, there are signal problems in some areas and not yet total coverage. The PIS-PK data analysis stage has not been carried out thoroughly. The stage of further intervention on health problems has not been carried out thoroughly by all PHC because the majority of PHC is still in the family visit stage. The monitoring and evaluation phase is carried out by most of the PHC from the PIS-PK preparation stage to family visits and initial intervention. Several PHC has carried out monitoring and evaluation up to the initial IKS analysis stage and advanced intervention. The implementation of PIS-PK in Banyuwangi is not fully following the guidelines for implementing the PIS-PK Regulation of the Minister of Health Republic Indonesia Number 39 of 2016.